Flipping theClassroom; Developing listening Material - Misela, Jenny Ika (Universitas Nusantara PGRI Kediri, 2016)
Flipped classroom is an approach to teach listening in which students participate in online learning in place of traditional homework and then attend school for face-to-face, teacher-guided practice or projects. It is a part of larger education system called blended learning. In this approach, students could learn new content on their own by watching video lectures or other online sources and assigned problems (traditional “homework”) are completed in class with teachers offering personalized guidance instead of lectures. The paper here examined an ESL listening class. Listening skill is much more than hearing. Unfortunately, in students’ opinion, listening is an uninteresting activity. Many students feel very bored in listening class. That is why teachers should know about how to make the students more interested in listening. The aim of this paper is discuss best practices and challenges of implementing the flipped classroom in teaching and learning listening. By using this approach, it is expected that students will develop their listening skills as well as have a lot of fun. The main findings of the study indicate that the students enjoyed learning listening in a flipped classroom environment. They can practice not only listening but also all language skills in listening class.